Vitamin D content and prevalence of vitamin D deficiency in patients with epilepsy: a systematic review and meta-analysis - Liu, Yuanyuan; Gong, Chao; Li, Jiawei; Ning, Xin; Zeng, Pei; Wang, Luchuan; Lian, Beibei; Liu, Jiahao; Fang, Liya; Guo, Jin (Frontiers in Nutrition, 2024)
The prevalence of vitamin D deficiency and vitamin D levels in patients with epilepsy (PWE) were systematically evaluated, and the differences between subgroups were analyzed. We identified all articles investigating the prevalence of vitamin D deficiency in patients with epilepsy from the database established in March 2024 from PubMed, Web of Science, and Embase. We divided them into anti-seizure medication (ASM) interventions and non-ASM interventions according to whether or not someone used ASM. A total of 68 articles were included. The prevalence of newly diagnosed epilepsy was 50.2%(95 % CI: 38.7% -61.7% ), and the prevalence after ASM intervention was 47.9%(95 % CI: 40% -55.9% ), including 7070 patients with epilepsy. Subgroup and meta-regression analyses were performed according to the diagnostic criteria, economic development level, region, age, ASM treatment, and other factors. The results showed that the differences were not significant. In addition, the vitamin D content of epilepsy patients (18.719ng/mL ) was lower than that of healthy people (20.295ng/mL ). The prevalence of vitamin D deficiency in patients with epilepsy is very high. Still, the related factors have little effect on the high prevalence of vitamin D in epilepsy, and ASM intervention can reduce the vitamin D content in patients with epilepsy. Therefore, it is emphasized that monitoring vitamin D levels is part of the routine management of patients with epilepsy.